2022
DOI: 10.1177/00469580221100157
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Physical Activity Among Healthcare Students in King Saud University, Riyadh, Saudi Arabia. An Observational Study

Abstract: Background and Objective Physical inactivity is 1 of the most important cardiovascular risk factors causing higher morbidity and mortality rate worldwide. Thus, the promotion of physical activity (PA) is 1 of the fundamental pillars in the primary prevention of heart disease. Therefore, this study aimed to assess the prevalence of Physical Activity among healthcare Students in the Riyadh region, Saudi Arabia. Methods An observational, descriptive, cross-sectional study using paper-based printed questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 33 publications
2
11
3
1
Order By: Relevance
“…Thus, keeping an adequate amount of physical exercise and decreasing sedentary time can be crucial in aiding individuals in coping with a significant life event, especially in the case of repeated lockdowns due to a pandemic outbreak. [28] A recent study [16] that examined the prevalence of physical activity among emergency medical students at the Prince Sultan College for Emergency Medical Services at King Saud University, Riyadh, Saudi Arabia, reported findings that were not similar to those of this study. The findings showed that almost 70% of their students (n = 123) engaged in physical activity, with running coming in third, followed by gym or bodybuilding.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Thus, keeping an adequate amount of physical exercise and decreasing sedentary time can be crucial in aiding individuals in coping with a significant life event, especially in the case of repeated lockdowns due to a pandemic outbreak. [28] A recent study [16] that examined the prevalence of physical activity among emergency medical students at the Prince Sultan College for Emergency Medical Services at King Saud University, Riyadh, Saudi Arabia, reported findings that were not similar to those of this study. The findings showed that almost 70% of their students (n = 123) engaged in physical activity, with running coming in third, followed by gym or bodybuilding.…”
Section: Discussioncontrasting
confidence: 82%
“…Recent studies used the same questionnaire and established reliability with Cronbach Alpha value of 0.85. [10,16] Physical activity intensity is measured in terms of metaphorical equivalents (MET). The term "MET" denotes the quantity of energy expended while one is still, and it is equivalent to 1 kcal/kg/ hour of calorie intake.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,21 In our study, the median sitting time was 3480 minutes/ week (or 8.29 hours/day), which was higher than that reported among medical students in Karnataka (2044 minutes/week) and Emergency medical service students in Saudi Arabia (3078.6 minutes/week). 21,24 However, medical students in North India have much higher values of 3696 minutes/week. 25 Excessive sitting time has been linked to a higher risk of allcause mortality and major cardiovascular diseases (CVD) such as cardiovascular death, myocardial infarction, stroke, or heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is widely documented that sedentary behavior is associated with people with overweight and obesity, hypertension, diabetes, and cardiovascular diseases. 49 Therefore, it is crucial to promote physical activity, given the links in the literature between sedentary lifestyles and poor health outcomes. [50][51][52] Furthermore, public health campaigns are an effective way of raising awareness of the value of physical activity in battling and preventing various weight-related diseases and discouraging sedentary behavior.…”
mentioning
confidence: 99%